Artificial Intelligence and the Zone of Proximal Development: Investigating ChatGPT as Digital Scaffolding in Arabic Language Learning - Nur Fuadi Rahman; Devi Rafika Sari; Edy Murdani Z; Muhammad Ainur Roziqi (Universitas Islam Negeri Palangka Raya Raya, 2026)
Learning Arabic as a foreign language is frequently characterized by episodes of regression, in which learners temporarily struggle to perform skills that were previously acquired. Within Vygotsky’s Zone of Proximal Development (ZPD), such regression may signal the need for scaffolding that enables learners to progress beyond their current level of competence. While recent studies have highlighted the growing use of artificial intelligence in language education, limited research has examined how ChatGPT functions as a form of digital scaffolding in supporting learners during periods of regression. This study investigates the role of ChatGPT as digital scaffolding in Arabic language learning among non-native speakers. Employing a descriptive qualitative exploratory design, the study involved 28 university students from different regions of Indonesia. Data were collected through semi-structured interviews and classroom observations and analyzed thematically. The findings indicate that ChatGPT operates as an adaptive, responsive, and dialogic scaffolding tool that assists learners in overcoming temporary learning difficulties, facilitating self-regulated learning, and promoting reflective engagement with Arabic language tasks. However, its support remains transitional rather than fully substitutive, as meaningful learning development continues to depend on authentic social interaction with teachers and peers. The study contributes to the emerging discourse on AI-mediated learning by conceptualizing ChatGPT as transitional digital scaffolding that supports learners’ progression from assisted performance toward greater autonomy within the ZPD framework.